New Perspectives on Intergovernmental Relations
XVII, 216 p. 9 illus.
Keywords: This open access book assesses the consequences of contemporary economic and political crises for intergovernmental relations in Europe. Focusing on the crises arising from the Covid-19 pandemic, climate change, surges in migration, and the resurgence of regional nationalist movements, it explores the shifting power balances within intergovernmental relations’ systems. The book takes a comparative analytical perspective on how intergovernmental relations are changing across Europe, and how central governments have responded to coordination challenges as recent crises have disrupted established service delivery chains and their underpinning political and bureaucratic arrangements. It also examines the relationship between recent crises and the sub-national resurgence of territorial politics in many European countries. The book will appeal to those with interests in public administration, sub-national governance and European politics. Sabine Kuhlmann is Professor of Political Sciences, Administration and Organization at the University of Potsdam, Germany. Martin Laffin is Professor of Public Policy and Management at Queen Mary University of London, UK. Ellen Wayenberg is Professor of Public Policy and Administration at Ghent University, Belgium. Tomas Bergström is Associate Professor of Political Science at Lund University, Sweden.